Some Results on Ultrametric-Metric-Preserving Functions - Delgadillo Piñon, Gerardo; Lopez De Luna, Miguel (JOURNAL OF BASIC SCIENCES, 2016)
Functions whose composition with every ultrametric is a metric are said to be ultrametric-metric-preserving. In this paper, some properties for this set of functions are provided. In addition, several results for this class of functions, that are not valid for functions that preserve the metric, are established. Some examples are given.